Do trabalho docente às políticas de readaptação profissional : o caso dos professores da Secretaria de Estado da Educação de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This study, anchored in the research line Education, School and Technologies of the Interdisciplinary Postgraduate Program in Education, Language and Technologies of the State University of Goiás, has as its theme the professional readaptation and the teaching work. It is known that during readaptation, the teacher is removed from exercising his/her job in the classroom and begins to perform other activities in the school. The majority of readapted teachers remain working in the places where they were assigned, performing activities that are consistent with the restrictions established in the medical report. In any case, the readaptation is expected to be temporary. However, the SEDUC spreadsheets show a large number of retirements due to disability.Hence, it is questioned: how is the teaching work done, its conditions and its impacts for teachers who experience the readaptation process? The methodology of the research is qualitative based, with a bibliographic literature review and triangulation between the current data of the state of Goiás, its articles and rules that deal with professional readaptation, in interaction with the responses of the participants. From that point on, our general objective was to analyze the teaching work, its conditions, and its impacts on teachers who go through the readaptation process. In this direction, three specific objectives were proposed: to understand the condition of the teaching work, its changes in the current context and its relationship with public policies; to discuss the state regulations aimed at professional readaptation in the educational field; and to unveil the readaptation policies for teachers. We raise the hypothesis that the policies aimed at teacher readaptation in the State of Goiás do not consider the working conditions and their impacts on teachers' health, promoting only a new professional relocation, leaving aside objective and subjective aspects that involve the teaching career. Eight (8) female teachers participated in the field research, aged between 41 and 74 years old, most of them with more than 20 years in the profession, permanently readapted in an administrative position, who experience/have experienced the readaptation policies of the education network of the State of Goiás.The results pointed out some latent issues: the first is that the rules provide rights to the readapted that, in practice, are not guaranteed; the second is that, although the readaptation is an opportunity given to the sick teacher to continue working, there is no effective program that provides the professional with a treatment that allows him/her to return to the exercise of the functions of his/her original position. The conclusion is that, although there are public policies that deal with rehabilitation and readaptation, they do not attack the root of the problem, which is the precariousness of the teaching work. They are important policies in terms of what they propose, but the desired result - which would be that the teacher who is sick goes through the process proposed by the policy and, when reassessed, it is verified that the physical and emotional weakness that caused his or her removal from teaching has been overcome, that the readapted teacher has recovered his or her labor capacity to perform the duties of his or her original position and can resume teaching - does not happen. For this, we suggest that the SEDUC continuously accompany the readapted teachers so that they can have a voice, that they are duly informed of their functional condition, that they can perform their teaching duties and receive the support they need.
From Teaching Work to the Public Policies of Professional Readapting : the case of teachers of the Secretary of Education of the State of Goiás
Keywords: Educação – Políticas públicas; Condições de trabalho docente; Educação – Adoecimento; Reabilitação e readaptação; Public Policies; Working Conditions; Teaching work; Illness; Rehabilitation and Readaptation; CIENCIAS HUMANAS::EDUCACAO